Maternal Smoking Intensity During Pregnancy and Early Adolescent Cardiovascular Health - Mengjiao Liu; Elna Yihui Soon; Katherine Lange; Markus Juonala; Jessica A. Kerr; Richard Liu; Terence Dwyer; Melissa Wake; David Burgner; Ling‐Jun Li (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The adverse cardiovascular effects of smoking are well established. We aimed to investigate the less well‐understood effects of pregnancy smoke exposure on offspring cardiovascular health in early adolescence. Methods and Results Data were drawn from the nationally representative Longitudinal Study of Australian Children's Child Health CheckPoint. Mothers reported mean daily cigarettes smoked in each trimester (≤10 versus >10/day), and smoking cessation during pregnancy. Blood pressure, pulse wave velocity, carotid intima‐media thickness, and retinal microvascular parameters were measured in early adolescence (mean 11.5 years). Hypertension was defined as systolic blood pressure ≥120 or diastolic blood pressure ≥80 mm Hg. 187 (11.8%) of 1582 women (mean age 30.7±0.2 years), smoked during pregnancy, of whom 143 (76.5%) smoked throughout pregnancy, and 58 (31.0%) smoked >10 cigarettes/day. Compared with those born to nonsmoking mothers, the odds of hypertension in early adolescence were 1.44 (95% CI, 1.01–2.06) if mothers ever smoked, 1.99 (1.22–3.24) if mothers smoked >10 cigarettes/day, and 1.64 (1.11–2.42) if mothers smoked throughout pregnancy There was limited evidence of associations between smoking throughout pregnancy and other cardiovascular measures. Offspring of mothers who stopped smoking during pregnancy and nonsmokers had similar cardiovascular measures, apart from hypertension. Conclusions Offspring of mothers who smoked in pregnancy have increased risks of hypertension in adolescence, with increased risk with greater exposure intensity and duration. Mothers who stopped smoking during pregnancy had offspring with similar cardiovascular health to those born to nonsmokers. Our findings underscore the importance of specific strategies to stop maternal smoking before conception and during pregnancy.